Awards - A View From Psychological Economics - Bruno S. Frey; Susanne Neckermann (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Awards in the form of orders, decorations, prizes, and titles are ubiquitous in monarchies and republics, private organizations, not-for-profit, and profit-oriented firms. This paper argues that awards present a unique combination of different stimuli and that they are distinct and unlike other monetary and non-monetary rewards. Despite their relevance in all areas of life awards have not received much scientific attention. We propose to study awards and present results on a vignette experiment that quantifies and isolates the effects of different award characteristics such as the publicity associated with winning an award. Further, employing a unique data set, we demonstrate that there are substantial differences in the intensity of usage of awards across countries.
Keywords: C93; J33; M52; 330; Awards; compensation; incentives; principal-agent; honors and distinctions